Disaster Learning Based on Local Wisdom Through a Simulation Learning Model Toward Students’ Disaster Preparedness in the Small Volcanic Island of Ternate - Syahril Lukman; Dahri Hi Halek; Revana Sakir; Rozana Eka Putri (Universitas Negeri Medan, 2026)
Ternate City is classified among the 170 regencies and cities identified as priority sites for disaster risk reduction by the Indonesian government, as designated by the National Disaster Management Agency (BNPB). This categorization is attributed to the geographic characteristics of Ternate Island, which is characterized as a small volcanic island featuring the active Gamalama Volcano, thereby presenting a significant disaster risk. These circumstances cause local residents, specifically junior high school students residing within the Gamalama Volcano Disaster-Prone Zone (Kawasan Rawan Bencana-KRB), to be particularly vulnerable to disasters. Therefore, the implementation of disaster education that incorporates the local wisdom of Ternate through a simulation-based learning model is crucial to enhance students’ preparedness and mitigate risks during potential disaster occurrences. This study aims to identify the level of disaster preparedness between an experimental group taught using a simulation learning model integrated with local wisdom-based disaster education and a control group taught using conventional learning. It also aims to compare the preparedness levels between both groups. The study employed a quasi-experimental method using a posttest-only control group design. The sample consisted of 192 students selected using cluster random sampling, consisting of 96 students in the experimental group and 96 students in the control group. Data analysis involved both descriptive quantitative analysis and comparative analytical techniques. The results indicate that the preparedness level of the experimental group was classified as “very ready,” with an index of 87.02. In contrast, the control group was categorized as “ready,” with an index of 73.58. Furthermore, the comparative analysis reveals that Sig. (2-tailed) = 0.000 < 0.05, suggesting a statistically significant difference between the two groups; hence, H0 is rejected while Ha is accepted. These findings confirm that the simulation learning model integrated with local wisdom-based disaster education significantly enhances student disaster preparedness in comparison to conventional educational methods.